Типи заходів з охорони атмосферного повітря - Соркіна, Діана Костянтинівна; Баранова, Антоніна Олегівна (Яроче́нко Я. В., 2022)
Standards and norms that are currently valid in the area of air protection are designed to implement safe modern technologies, prevent man-made disasters and accidents, and are a guarantor of a safe environment. Businesses, organizations and citizens who are business entities must implement measures to ensure compliance with the requirements in the area of air protection, provided by the norms and standards of environmental safety. Legislation obliges businesses to take measures to reduce emissions of pollutants and reduce the impact of physical factors.
Keywords: атмосферне повітря; охорона; екологія; технологічні заходи